Program strategy and coalition building as facets of new public management - Marsh, Ian (1999)
This paper explores two issues: first, the strategic and coalition-building tasks that may be routinely associated with New Public Management (NPM); and second, the implications of acknowledging these tasks for the conception of public management. NPM focuses on performance. It invites managers to accept responsibility for whole programs or systems (Kettle, 1997; Dunleavy, 1994; Ridley, 1996; Hood, 1995). This directs attention to basic program frameworks (that is, program strategy), as well as to operations. It involves the purposes of programs. It involves routine attention to such factors as the effectiveness of outcomes, the identification of alternative program configurations, the implications of emerging issues and needs, and the mobilisation of authority for change. In practice, this authority derives both from program stakeholders, as well as from ministers and the broader political system. - Reproduced
Keywords: Public administration - Australia; Public administration